Optical Coherence Tomography Angiography Detects Choriocapillaris Loss in Decalcification of Choroidal Osteoma. (July 2019) - Hoshiyama, Ken; Nakao, Shintaro; Shiose, Satomi; Yoshikawa, Hiroshi; Kano, Kumiko; Kaizu, Yoshihiro; Murata, Toshinori; Sonoda, Koh-Hei
Purpose: Choroidal osteoma, which typically affects young women, is a benign intraocular tumor composed of mature bone within the choroid. Tumor decalcification and subfoveal choroidal neovascularization often lead to poor visual acuity although the etiology is unknown. Choriocapillaris characteristics in choroidal osteoma also are unknown. Methods: We report 4 cases of choroidal osteoma with decalcification in which the choriocapillaris could be imaged by optical coherence tomography angiography (OCTA). Results: OCTA showed that the choriocapillaris structure was maintained in the calcified portion, whereas a loss occurred in parts of the decalcified portion in all cases. Conclusions: OCTA may be useful for understanding the pathological states of choroidal osteoma.